Modelling film and rivulet flows on microstructured surfaces using CFD methods. (6th April 2022) - Bertling, R.; Hack, M.; Ausner, I.; Horschitz, B.; Bernemann, S.; Kenig, E.Y.
Highlights: Numerical investigation of film and rivulet flow on packing sheets with different surface structures. A new method for the identification of effective contact angles. A new modelling approach was proposed for the description of perforated surfaces. The model was successfully validated against experimental data. Abstract: A new procedure to identify effective contact angles used in the description of the packing surface wetting is proposed. Both non-perforated and perforated surfaces are modelled. The flow of a water and triethyleneglycol (TEG) mixture over inclined, non-corrugated packing sheets was used as a model case. Different microstructures were investigated in a combined experimental and numerical study to determine the effective contact angles best reproducing the experimental film or rivulet widths. The outcome is a simple yet robust approach for modelling the liquid flow on structured packings.